Is the world flat or not (yet)?: trade globalization and digitalization - Simões, N.; Palan, N.; Crespo, N. (Handbook of research on institutional, economic, and social impacts of globalization and liberalization, 2021)
This chapter adds to the understanding of trade globalization by accounting for the complexity and multi-dimensionality of the phenomenon at hand. This approach captures different aspects of the phenomenon, such as the interconnectedness of countries, geographical distance, and sectoral trade relationships over a period of 50 years. Thereby both the commonalities and differences in the long-term trends for the individual dimensions of trade globalization are highlighted. Results indicate that regarding the number of positive bilateral trade flows, globalization was almost completed by 2016. Also, distance diminished significantly in importance for trade relationships. Yet, data shows that the degree of globalization was significantly different for high-tech sectors compared to low-tech sectors even though the latter could catch up over time. During recent years, protectionism tendencies have led to the discussion about a new age of slowbalization to be on the way while digitalization processes can integrate countries even further into global production and trade networks.